2014
DOI: 10.1111/jon.12101
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Fractional Flow on MRA Predicts Stroke Risk of Intracranial Stenosis

Abstract: Background and purpose: Fractional flow may identify hemodynamic effects and ischemic risk beyond percent stenosis of an artery. We hypothesized that diminished TOF-MRA signal intensity distal to an intracranial stenosis predicts stroke risk. Methods: TOF-MRA was acquired prospectively in the SONIA-WASID trials. The distal/proximal signal intensity ratio (SIR) was calculated from 3 mm regions of interest, blinded to outcome. Univariate and multivariate analyses included clinical variables, SIR, and invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 19 publications
1
66
1
Order By: Relevance
“…Leng et al [31] demonstrated on CFD models that the translesional pressure gradient has a trend towards being able to predict recurrent ischemic stroke risk in the territory of the treated artery within 1 year. Liebeskind et al [32] reported that the use of the signal intensity ratio index, calculated from the change of signal intensities based on flow-related contrast enhancement on time-of-flight MRA images, was associated with recurrent stroke in the territory of the stenotic artery, irrespective of the anatomical stenosis severity. These noninvasive methods, though attractive, are also in the initial phase of development and are not without their own limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Leng et al [31] demonstrated on CFD models that the translesional pressure gradient has a trend towards being able to predict recurrent ischemic stroke risk in the territory of the treated artery within 1 year. Liebeskind et al [32] reported that the use of the signal intensity ratio index, calculated from the change of signal intensities based on flow-related contrast enhancement on time-of-flight MRA images, was associated with recurrent stroke in the territory of the stenotic artery, irrespective of the anatomical stenosis severity. These noninvasive methods, though attractive, are also in the initial phase of development and are not without their own limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the signal intensity on TOF MRA proximal and distal to a symptomatic intracranial stenosis may be a reasonable measure of fractional flow reserve associated with the stenosis. A post-hoc analysis of patients in the WASID and SONIA trials suggests that patients with distal to proximal signal ratios of less than 0·9 on TOF MRA are at a higher risk of stroke than are those with ratios of 0·9 or greater 124 .…”
Section: Future Directionsmentioning
confidence: 99%
“…The index SIR of ICAS on TOF-MRA has been demonstrated to be of high inter-observer reproducibility, as reported in our previous study [12]. In theory, SIR across an ICAS may reflect hemodynamic features of the stenosis, and has been proven to be associated with recurrent stroke in the relevant territory in patients with symptomatic ICAS [11,14,17]. However, the capacity of SIR to represent the hemodynamic changes of stenosis needed to be verified, so that it could be further utilized in assessment and risk stratification of affected patients.…”
Section: Discussionmentioning
confidence: 75%
“…1) [11,12,14]. In brief, SIs proximal or distal to a target lesion were measured on MRA by outlining a 3-mm-length region of interest (ROI) covering the arterial lumen.…”
Section: Methodsmentioning
confidence: 99%